2017
DOI: 10.1017/laq.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Domestic Ceramic Production in the Maya Lowlands: A Case Study From Uxbenka, Belize

Abstract: Utilitarian ceramic vessels form the bulk of artifact assemblages in the Maya Lowlands, but little is known about their production beyond the likelihood that they were made in a domestic context without elite involvement. Characterizing the production and distribution of these vessels is vital to understanding ancient Maya economic systems; nevertheless, this is a difficult task in the absence of primary production locales. We use spatial data, use-wear analyses on stone and ceramic tools, and analyses of fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These data support Hirth's (2009a:15) argument that craft production does not correspond with resource stress in Mesoamerican archaeological contexts. It is important to keep in mind that poverty associated with many modern potters (Arnold 1985:226; Deal 1998:25; Jordan and Prufer 2017; Stark 1991) may be a consequence of modern world systems, the legacies of colonialism, and modern government policies (Nash 1993:130). Nash (1993:130), for example, has observed that in modern times the “intensification of production done in the home has occurred in rural areas throughout Mexico as a result of the shrinking land base for indigenous communities and a rising population.”…”
Section: Discussion: Household Productionmentioning
confidence: 99%
“…These data support Hirth's (2009a:15) argument that craft production does not correspond with resource stress in Mesoamerican archaeological contexts. It is important to keep in mind that poverty associated with many modern potters (Arnold 1985:226; Deal 1998:25; Jordan and Prufer 2017; Stark 1991) may be a consequence of modern world systems, the legacies of colonialism, and modern government policies (Nash 1993:130). Nash (1993:130), for example, has observed that in modern times the “intensification of production done in the home has occurred in rural areas throughout Mexico as a result of the shrinking land base for indigenous communities and a rising population.”…”
Section: Discussion: Household Productionmentioning
confidence: 99%
“…The smaller social units in the vast communities in which we live today create a sense of social solidarity and connect us to others both geographically and socially. In these residential clusters, the Classic Maya may have similarly developed a deeper sense of community based on shared experiences [ 51 ], but this requires further investigations of artifact classes, architectural patterns and spaces for aggregation, burial and caching practices, and communities of practice within neighborhoods of a single center [e.g., 9 , 12 , 15 , 19 , 186 , 194 , 195 ]. Neighborhoods provide access to corporate and kin-held property, labor, resources, and identities, all of which underpin everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for household production, including the identification of ceramic manufacturing areas or the presence of related tools (e.g. Jordan & Prufer 2017) is absent. A compositional correlation between late Middle Preclassic Jocote vessels and earlier Cunil utilitarian wares, however, suggests that both types were produced locally for domestic consumption.…”
Section: Discussionmentioning
confidence: 99%